2008
DOI: 10.1152/ajpcell.00461.2008
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localization, and functional properties of Bestrophin 3 channel isolated from mouse heart

Abstract: Bestrophins are a novel family of proteins that encode calcium-activated chloride channels. In this study we establish that Bestrophin transcripts are expressed in the mouse and human heart. Native mBest3 protein expression and localization in heart was demonstrated by using a specific polyclonal mBest3 antibody. Immunostaining of isolated cardiac myocytes indicates that mBest3 is present at the membrane. Using the patch-clamp technique, we characterized the biophysical and pharmacological properties of mBest3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 54 publications
(84 reference statements)
4
54
0
Order By: Relevance
“…Bestrophin-3, when expressed in HEK cells, was activated by Ca 2+ with the K d of 175 nmol/L, and blocked by micromolar concentrations of DIDS and niflumic acid [62]. The cellular expression of Bestrophin-3 in murine ventricular cells showed a punctuated pattern which was strong in the sarcolemma [62]. In our images obtained in canine ventricular myocytes the cellular expression of Bestrophin-3 showed striated pattern rather than being punctuated.…”
Section: Ca 2+ -Entry Via I Cal Is Essential For the Activation Of Imentioning
confidence: 56%
See 2 more Smart Citations
“…Bestrophin-3, when expressed in HEK cells, was activated by Ca 2+ with the K d of 175 nmol/L, and blocked by micromolar concentrations of DIDS and niflumic acid [62]. The cellular expression of Bestrophin-3 in murine ventricular cells showed a punctuated pattern which was strong in the sarcolemma [62]. In our images obtained in canine ventricular myocytes the cellular expression of Bestrophin-3 showed striated pattern rather than being punctuated.…”
Section: Ca 2+ -Entry Via I Cal Is Essential For the Activation Of Imentioning
confidence: 56%
“…The same group reported the expression of Bestrophin-3 in murine and human heart (although only at mRNA level in the latter) similarly to Bestrophin-1 [62]. Bestrophin-3, when expressed in HEK cells, was activated by Ca 2+ with the K d of 175 nmol/L, and blocked by micromolar concentrations of DIDS and niflumic acid [62]. The cellular expression of Bestrophin-3 in murine ventricular cells showed a punctuated pattern which was strong in the sarcolemma [62].…”
Section: Ca 2+ -Entry Via I Cal Is Essential For the Activation Of Imentioning
confidence: 90%
See 1 more Smart Citation
“…The molecular identity of CACCs in the heart remains to be determined. CLCA-1 and bestrophins were initially proposed as candidates for CACCs in cardiac tissues (Hartzell et al, 2005;O'Driscoll et al, 2008). It has been demonstrated that at least three members of the murine Bestrophin family, mBest1, mBest2 and mBest3, are expressed in mouse heart.…”
Section: +mentioning
confidence: 99%
“…It has been demonstrated that at least three members of the murine Bestrophin family, mBest1, mBest2 and mBest3, are expressed in mouse heart. Whole-cell patch clamp experiments with HEK cells transfected with cardiac mBest1 and mBest3 both elicited a calcium sensitive, time independent Cl -current, suggesting mBest1 and mBest3 may function as pore-forming Cl -channels that are activated by physiological levels of calcium (O'Driscoll et al, 2008). Very recently, independent studies from three laboratories have identified a new gene, TMEM16 (or Ano1), as a candidate for CACCs (Schroeder et al, 2008;Caputo et al, 2008;Yang et al, 2008).…”
Section: +mentioning
confidence: 99%